Differential oxido-reductive activities of aged garlic extract and S-allyl-cysteine in genetically modified Drosophila model of Alzheimer's disease. - Afolayan, O.; Nwaogu, V.; Idowu, O.; Dosumu, O. (BMC complementary medicine and therapies, 2025)
Alzheimers disease (AD) is a progressive neurodegenerative disorder frequently associated with ageing. It is characterised by the loss of neurons in the hippocampus and cortex, leading to declines in cognitive function and memory. Recent research has spotlighted Aged Garlic Extract (AGE) and its bioactive component, S-allyl-cysteine (SAC), as promising candidates for the treatment of AD due to their potent antioxidant, anti-inflammatory, and neuroprotective properties. These features help mitigate oxidative stress and neuronal damage associated with the disease. The present study aimed to evaluate the neuroprotective effects of AGE and SAC using a Drosophila melanogaster (Drosophila) model of Alzheimers disease. The Drosophila (UAS-A? > Elav-GAL4) were reared on a diet supplemented with varying concentrations of AGE (10 µL, 20 µL, and 40 µL) and SAC (at doses of 25, 50, and 75 mg/kg). Key parameters measured included larval motility, negative geotaxis, and oxidative stress markers. The AD models exhibited reduced motor abilities, decreased antioxidant levels, increased oxidative stress, and elevated acetylcholinesterase (AChE) activity. However, treatment with different concentrations of AGE and SAC significantly improved locomotor function and modulated redox activities, along with a reduction in AChE activity. This study highlights the neuroprotective potential of AGE and its active component, SAC, in the Drosophila AD model, indicating that the beneficial effects of AGE are primarily attributed to SAC.